Marital satisfaction of visually impaired couples - Nur Zahra, Suaidi; Jamayah, Saili (Indonesian Counselor Association (IKI), 2019)
Despite the relatively high degree of research among disabilities in Malaysia, there remains lack of research on issues and challenges faced by visually impaired couples. Visually impaired couples may experience different set of challenges and seek different needs for a satisfying married life as compared to typical couples. The research was conducted qualitatively by interviewing four visually impaired couples. The analysis of in-depth interviews with the couples yields three main themes which are the challenges, the coping strategies, and the future hopes of the visually impaired couples.